INSERTED CONSTRUCTIONS IN SPOKEN DISCOURSE AND THEIR FUNCTIONAL-SEMANTIC NATURE (Web of Teachers: Inderscience Research, 2025)
This paper examines inserted constructions functioning in spoken discourse from a comparative-theoretical perspective based on Korean and Uzbek. Inserted constructions are considered pragmatically marked units that are not syntactically integrated into sentence structure but significantly influence discourse coherence. The research identifies their principal functional and semantic types and outlines language-specific as well as universal characteristics observed in oral communication.